PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PERUSAHAAN (STUDI PADA PERUSAHAAN PULP & PAPER YANG TERDAFTAR DI BEI PERIODE 2014 SAMPAI DENGAN 2018) - Aprilya, Megi; Gusnardi, Gusnardi; RM. Riadi, RM. Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to investigate the influence of Corporate SocialResponsibility on the company's financial performance. The population in this study areall Pulp & Paper manufacturing companies listed on the Indonesia Stock Exchange thathave data (disclosure of Corporate Social Responsibility and company financialperformance) from 2014 to 2018. This study uses secondary data. The data collectiontechnique used is documentation technique. The data analysis technique used in thisresearch is simple linear regression. The results show that Corporate SocialResponsibility affects the company's Return On Asset.Key Words: Corporate Social Responsibility, Return On Asset